ANALISIS PERBANDINGAN KUALITAS LAYANAN JARINGAN 4G LTE TELKOMSEL BERDASARKAN PADA PERIODE WEEKDAY DAN WEEKEND DI KECAMATAN BUNGUS TELUK KABUNG, KOTA PADANG - Mailani, Sri (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
The rapid development of 4G LTE technology is often challenged by dynamic traffic patterns, particularly in tourist areas like Bungus Teluk Kabung, Padang. This research aims to analyze and compare the Quality of Service (QoS) of Telkomsel's 4G LTE network during weekday and weekend periods. Data collection was conducted using the drive test method with TEMS Pocket 2 software in dedicated mode to measure key parameters: RSRP, RSRQ, SINR, and throughput. The results indicate a significant difference in network performance between the two periods. While signal coverage (RSRP) remained stable and "Good" (above 55%) in both timeframes, throughput experienced a sharp degradation during weekends. On weekdays, 61.5% of samples were in the "Good" throughput category, whereas on weekends, "Poor" samples (< 512 kbps) surged to 34.94%. This decline is strongly correlated with increased interference and network congestion caused by the surge of users in tourist spots. The study concludes that network issues are driven by capacity limitations rather than coverage, requiring infrastructure optimization to handle peak weekend loads.